Posterior Reversible Encephalopathy Syndrome in ALL - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators from Soochow University, Suzhou, China, studied the possible pathogenetic mechanisms and treatment of posterior reversible encephalopathy syndrome (PRES) observed in 11 cases of pediatric acute lymphoblastic leukemia (ALL) after induction chemotherapy.